A "Boil" Being the Clue to Think beyond Typical Bacterial Pathogens in Community-Acquired Pneumonia - Jeanna Auriemma (Hindawi Limited, 2022)
Empyema necessitans is an exceptionally rare complication of bacterial pneumonia in the pediatric population. It occurs when the infection extends from the lung parenchyma to the chest wall by forming a fistula, which leads to infection of the surrounding soft tissue. In this case, a 13-year-old boy is found to have empyema necessitans caused by Actinomyces meyeri, with a preceding clue to the diagnosis being that he was treated for a superficial chest wall abscess several weeks prior to developing significant respiratory symptoms. Providers should be aware of this entity as it requires obtaining cultures to identify the appropriate pathogen and avoid treatment failure as it has implications for antibiotic choice and length of therapy.